2011
DOI: 10.1088/0004-637x/733/2/115
|View full text |Cite
|
Sign up to set email alerts
|

The Color-Period Diagram and Stellar Rotational Evolution—new Rotation Period Measurements in the Open Cluster M34

Abstract: We present the results of a 5-month photometric time-series survey for stellar rotation periods combined with a 4-year radial-velocity survey for membership and binarity in the 220 Myr open cluster M34. We report surface rotation periods for 120 stars, 83 of which are kinematic and photometric late-type cluster members. A comparison to previous work serves to illustrate the importance of 1 WIYN Open Cluster Study XLV

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(126 citation statements)
references
References 78 publications
(108 reference statements)
7
119
0
Order By: Relevance
“…This study also revealed a strong correlation between the saturated and non-saturated regimes of X-ray emission and the C and I rotation sequences observed in M 34 (Irwin et al 2006;James et al 2010;Meibom et al 2011). Using the CgI sequence classification of M 35 stars by M09, a second set of X-ray luminosity distributions was calculated assuming that C-sequence and gap stars emit X-rays at the R X,sat saturation level and that I-sequence stars emit X-rays in the non-saturated regime.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This study also revealed a strong correlation between the saturated and non-saturated regimes of X-ray emission and the C and I rotation sequences observed in M 34 (Irwin et al 2006;James et al 2010;Meibom et al 2011). Using the CgI sequence classification of M 35 stars by M09, a second set of X-ray luminosity distributions was calculated assuming that C-sequence and gap stars emit X-rays at the R X,sat saturation level and that I-sequence stars emit X-rays in the non-saturated regime.…”
Section: Discussionsupporting
confidence: 64%
“…In a recent paper, Gondoin (2012;hereafter G12) reported a correlation between the saturated and non-saturated regime of X-ray emission and the C A&A 556, A14 (2013) and I rotation sequences that have been observed in M 34 from extensive rotation periods surveys (Irwin et al 2006;James et al 2010;Meibom et al 2011). Messier 34 sample stars also show a steep transition in X-ray to bolometric luminosity ratio between the C-sequence and gap stars that emit close to the 10 −3 saturation level, and the I-sequence stars, whose L X /L bol ratio is significantly lower for similar values of the Rossby number.…”
Section: Introductionmentioning
confidence: 95%
“…Detection was made of 189 X-ray sources that are listed in the XMM − Newton Serendipitous Source Catalog (Watson et al 2009). This list of X-ray sources was correlated with lists of M34 cluster members with known rotation periods established by Meibom et al (2011), Irwin et al (2006), and James et al (2010). In total, 41 single stars in the M34 open cluster have been found that have known rotational periods and detected X-ray emissions (Gondoin 2012).…”
Section: X-ray Observations Of the M34 Open Clustermentioning
confidence: 98%
“…Figure 1 (left) shows the rotational periods P of the sample stars as a function of their reddening corrected (B − V) 0 indices. The color-period diagram also displays the I and C rotational sequences of M34 along the form established by Barnes (2007) and Meibom et al (2011). The proximity of the M34 data points to these curves was used to determine their membership to the I sequence, to the C sequence or to the gap.…”
Section: X-ray Observations Of the M34 Open Clustermentioning
confidence: 99%
“…Among these properties are a cluster's turn-off age and average metallicity and also the lithium abundance and dispersion of its G dwarfs in order to relate eventual models to the Sun as a star. While space-based photometry is clearly superior for periodicities of various sorts, ground-based multi-band photometry and follow-up spectroscopy are essential in determining membership, abundances, and binarity (see, e.g., Meibom et al 2011;Milliman et al 2014). We have therefore used the A&A 580, A66 (2015) Herzog et al (1975) CoRoT satellite (Baglin et al 2006) in its sixth long run to observe selected and bona fide member stars of the open cluster IC 4756 that happened to be within the exoplanet field of view of the satellite.…”
Section: Introductionmentioning
confidence: 99%